2020
DOI: 10.15694/mep.2020.000036.1
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of simulation-based dental education

Abstract: In order to meet the needs of student learning within a competency-based pedagogy, it is necessary to understand the current philosophies and modalities being used in dental and oral health simulation-based education. The aim of this literature review is to identify the existing research relating to the educational structure of dental and oral health simulation activities. The review is presented as a scoping review, formulated and conducted using a modified five stage methodological framework. Despite evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…This will help to improve the students training experience as well as enhance their expertise in rehabilitating CPD cases once they graduate. In the era of e‐learning, simulation‐based learning by interactive software program can be encouraged that would expose the students to designing dentures in various different clinical scenarios, thus helping them in clinical practice even if they have not treated a multitude of patients in actual clinical setting 24 …”
Section: Discussionmentioning
confidence: 99%
“…This will help to improve the students training experience as well as enhance their expertise in rehabilitating CPD cases once they graduate. In the era of e‐learning, simulation‐based learning by interactive software program can be encouraged that would expose the students to designing dentures in various different clinical scenarios, thus helping them in clinical practice even if they have not treated a multitude of patients in actual clinical setting 24 …”
Section: Discussionmentioning
confidence: 99%
“…This research reveals that contemporary healthcare simulation curriculum designs are built on frameworks and supported by educational theories. A scoping review 56 has previously identified a lack of literature that explicitly states foundational frameworks and educational theories associated with dental simulation research. Further, there are many unique considerations to simulation‐based education within the dental context.…”
Section: A Framework For Simulation‐based Dental Educationmentioning
confidence: 99%
“…18 Jeffries highlighted five key concepts of simulation design, namely the use of clear objectives to guide simulation learning, fidelity or approximation to clinical reality, range in task complexity with varying levels of uncertainty and relevant information, the provision of cues and prompts if students are unable to process the situation, and debriefing. 19 While simulation design has been assessed in medical and nursing education, there is little literature on simulation design in dental education, 20,21 let alone in the home-based setting.…”
Section: Introductionmentioning
confidence: 99%